QUBIC: Exploring the Primordial Universe with the Q&U Bolometric Interferometer - Mennella, Aniello; Barbaràn, Gustavo; Bonaparte, Juan; Di Donato, Andrés Leonardo; Etchegoyen, Alberto; Fasciszewski, Adrián; Gamboa Lerena, Martin Miguel; Garcia, Beatriz Elena; Gómez Berisso, Mariano; González. Manuel; Luterstein, Raùl Horacio; Harari, Diego Dario; et al. (Multidisciplinary Digital Publishing Institute, 2019)
Fil: Mennella, Aniello. University of Milan; Italia